Research to support sustainable groundwater development and governance in Laos - Pavelic, Paul; Villholth, Karen G. (CGIAR Research Program on Water, Land and Ecosystems, 2019)
Lao PDR (Laos) is a landlocked country of around seven million people situated in the heart of the Mekong region (Fig. 1). Listed amongst the 47 UN-designated Least Developed Countries, its level of socioeconomic development is comparable to that of neighboring Myanmar and Cambodia but significantly lower than China, Thailand and Vietnam. Subsistence farming is the primary means of food security and income for nearly 80% of all households. Poorly developed, water-rich countries such as Laos have historically paid most attention to surface water resources, with limited consideration to groundwater.